Implementasi Penilaian Berbasis Portofolio Untuk Meningkatkan Aktivitas dan Hasil Belajar Mahasiswa Semester 1 Pendidikan Matematika STKIP Muhammadiyah Kuningan - Nuraeni, Zuli (Jurnal Gantang, 2019)
This study is a classroom action research (CAR) with research subjects of the first semester students of mathematics education STKIP Muhammadiyah Kuningan. This study aims to improve the quality of the process and activities and learning outcomes of students in the Introduction to Mathematics Basics 2017/2018 academic year. The research was carried out through 2 cycles. In the pre-test the average score achieved was 43, in the first cycle the average value became 68.4 increased by 25.4 or by 59%, whereas in the second cycle the average value became 90 increased by 21.6 from the first cycle or amounting to 31.58%. The average classical activity value in cycle I was 72.36 while in cycle II it increased 12.74 to 85.1, an increase of 17.61%. The average portfolio value in the first cycle was 77.80 while in the second cycle it increased 8.43 to 86.24, an increase of 10.84%. The results of the study show that learning with portfolio-based assessment can increase student activity and learning outcomes.